Company Value: Interest Rate, Financial Distress, And Reputation of KAP - Saputri, Nathasya Yemima; Widiyati, Dian (GOVERNORS, 2022)
The value of the company is important, the higher the investment rate, the better the value received by the Bank. For example, in banking companies, interest rates can influence people to save funds. Thus, the selected bank will be trusted by customers and investors to increase. Financial distress at the Bank will affect the value of the company, judging by the ability to pay its obligations smoothly. The current phase of financial distress is triggered by the Covid-19 Pandemic. The financial sector, particularly banking, is in the public's spotlight in mitigating the possibility of the worst happening. Banking assessments can also be accepted from KAP assessments based on the banking financial statements themselves. The research that will be used is the quantitative associative approach, which is to describe systematically, the accuracy of facts, and characteristics regarding the effect of interest rates, financial distress and KAP reputation on firm value. The data in this study were obtained from the official website of the Indonesia Stock Exchange, namely www.idx.com as well as several official banking websites from 2018 to 2021. The conclusion of the study based on EViews 9 with sample data of 20 banking companies concluded that empirically the interest rate has an insignificant effect on firm value. Empirical research on financial distress and KAP reputation has a significant influence on the company. Simultaneously, it is proven empirically that interest rates, financial distress, and KAP reputation have a significant effect on firm value.